(untitled) (Bangladesh Journal of Child Health, 2010)
Introduction: Popular Swenson’s pull through (1948) is still the most commonly practiced ’Gold Standard’ of operative treatment for rectosigmoid hirschsprung’s disease (HD). But minimally invasive transanal endorectal pull through (TERPT) is now being increasingly practiced worldwide for its treatment in many centers. Here we are describing our comparative experience between TERPT and Swenson’s pull through, at Dhaka Shishu Hospital to show the per-operative advantages of the former over the latter. Materials and methods: It is a prospective study at Dhaka Shishu Hospital during January 2000 to December 2001 in 32 (age, body weight and resected Rectosigmoid length matched) biopsy confirmed patients of HD divided into two Groups: Gr. A (na = 16) and Gr. B (nb = 16) patients who underwent TERPT and Swenson’s pull through respectively. Unpaired ’t’ and χ2 (with Yate’s correction) tests were used for statistical analysis whereas operative duration, volume of blood loss and transfusion requirements were used as parameters of the study. Results: For study Group A (TERPT) - operative time, volume of blood loss and transfusion requirement were significantly lesser (P < 0.01, P < 0.001 and P < 0.001 respectively) than the control Group B (Swenson’s procedure). Conclusions: Through this small comparative study, TERPT was found to be more advantageous than the Swenson’s pull through procedure in terms of operative duration, blood loss and transfusion requirement. Key words: TERPT; Swenson’s; Compare. DOI: 10.3329/bjch.v31i1.6068 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 12-15